1985
DOI: 10.1523/jneurosci.05-01-00072.1985
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of serotonin-immunoreactive cell bodies and processes in the abdominal ganglion of mature Aplysia

Abstract: Sensitization of the gill withdrawal reflex in Aplysia californica is an elementary form of learning, in part resulting from presynaptic facilitation of the LE mechanoreceptor neurons of the abdominal ganglion. It has previously been established that either application of serotonin or direct stimulation of a group of facilitatory neurons, the L29 cells of the abdominal ganglion, can simulate the effect of physiological stimulation in producing presynaptic facilitation. Because the evidence that serotonin serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
65
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 8 publications
15
65
1
Order By: Relevance
“…Stimuli that produce dishabituation of the withdrawal reflex, such as tail shock, activate facilitatory interneurons, some of which are serotonergic (Glanzman et al, 1989;Mackey et al, 1989;Marinesco and Carew, 2002). Release of 5-HT onto sensory and motor neurons within the CNS of Aplysia (Kistler et al, 1985;Marinesco and Carew, 2002;Zhang et al, 2003) causes rapid-onset presynaptic facilitation via processes that involve PKA and PKC [see Byrne and Kandel (1996) for details]. The strength of the presynaptic facilitatory processes wanes rapidly after washout of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli that produce dishabituation of the withdrawal reflex, such as tail shock, activate facilitatory interneurons, some of which are serotonergic (Glanzman et al, 1989;Mackey et al, 1989;Marinesco and Carew, 2002). Release of 5-HT onto sensory and motor neurons within the CNS of Aplysia (Kistler et al, 1985;Marinesco and Carew, 2002;Zhang et al, 2003) causes rapid-onset presynaptic facilitation via processes that involve PKA and PKC [see Byrne and Kandel (1996) for details]. The strength of the presynaptic facilitatory processes wanes rapidly after washout of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serotonergic processes have been shown to contact both sensory and motor neurons within the central ganglia of Aplysia (Kistler et al, 1985;Marinesco and Carew, 2002;Zhang et al, 2003). Finally, release of 5-HT is required for dishabituation and sensitization of the defensive withdrawal reflex in Aplysia (Glanzman et al, 1989).…”
Section: -Ht-induced Facilitation Depends On Postsynaptic Exocytosismentioning
confidence: 99%
“…Facilitation of SN-MN transmission can also be induced by intracellular stimulation of interneurons L29 and L28 (Hawkins 1981a,b). These interneurons act directly on siphon SNs using an unknown transmitter; it has been determined that the transmitter is not 5-HT (Kistler Jr. et al 1985;Hawkins and Schacher 1989). Finally, an increasing amount of evidence indicates that, in addition to heterosynaptic processes involving the release of modulatory transmitters onto the neuronal circuit, homosynaptic activity-dependent plasticity also occurs during learning, namely posttetanic potentiation (Walters and Byrne 1984;Frost et al 1988;Schacher et al 1990;Bristol et al 2001) and long-term potentiation (Murphy andGlanzman 1996, 1997;Antonov et al 2001Antonov et al , 2003.…”
Section: Modulation Of Defensive Reflex Circuits By 5-ht During Sensimentioning
confidence: 99%
“…Moreover, sensitizing stimulation leads to release of serotonin (Levenson et al 1999;Marinesco and Carew 2002). Previous studies using immunocytochemistry and electron microscopy demonstrated contacts between serotonergic processes and the cell body and processes of sensory neurons (Kistler Jr. et al 1985;Zhang et al 1991), but little is known regarding the relationship of serotonergic inputs to sensorimotor contacts. Using confocal microscopy as described above, we examined the relationship of serotonergic axons to pairs of sensory and motor neurons.…”
Section: Proximity Of Serotonergic Input To Sensorimotor Contactsmentioning
confidence: 99%
“…Morphological evidence indicates that serotonergic neurons provide input to sensory neurons Kistler Jr. et al 1985;Zhang et al 1991). The structural proximity of serotonergic processes would enable elevated levels of intracellular second messengers and activated protein kinases to diffuse to nearby synapses and phosphorylate target proteins.…”
mentioning
confidence: 99%